Answer: " x = - 2.5 " .
___________________________________________
Step-by-step explanation:
Given:
9(3x + 7) - 3.5 = - 8 ; Solve for "x" ;
First: Let us add "3.5" ; to both sides of the equation:
9(3x + 7) - 3.5 = - 8 ;
+ 3.5 = + 3.5 ;
___________________________________________
to get:
9(3x + 7) = - 4.5 ; [Note that " -3.5 + 3.5 = 0" ; [Cancels out to "0".].
Second: Let us expand the expression on the "left-hand side" of the equation.
" 9(3x + 7) " ;
Note the "distributive property" of multiplication:
" a(b + c) = ab + ac " ;
As such:
9(3x + 7) = 9(3x) + 9(7) = 27x + 63 ;
Third:
Now, replace this term for the original expression, on the "left-hand side" of the equation; & Rewrite the equation:
27x + 63 = - 4.5 ;
Fourth: Now, we can divide each side of the equation by "9" ;
(27x + 63) / 9 = (-4.5)/9 ;
to get:
(27x/9) + (63/9) = (-4.5/9) ;
to get:
3x + 7 = -0.5 ;
Fifth:
Subtract "7" ; from Each side of the equation:
3x + 7 = -0.5 ;
- 7 = - 7 ;
___________________________________________
to get:
3x = -7.5 ; [Note that " +7 - 7 = 0" ; [Cancels out to "0".] ;
___________________________________________
Sixth: Divide each side of the equation by "3";
to isolate "x" on one side of the equation; & to solve for "x" ;
___________________________________________
3x / 3 = -7.5 / 3 ;
to get:
x = - 2.5 .
___________________________________________
Hope this helps!
Best wishes!
___________________________________________